Hantavirus Pulmonary Syndrome: Report of the first three cases in São Paulo, Brazil - Marcos Vinicius da SILVA; Marileide Januária VASCONCELOS; Neuma Terezinha Rossetto HIDALGO; Ana Paula Rocha VEIGA; Mauro CANZIAN; Paulo Cesar Fumagali MAROTTO; Vasco Carvalho Pedroso de LIMA (Revista do Instituto de Medicina Tropical de São Paulo, 1997)
The hantavirus pulmonary syndrome was first recognized in cases that occurred in the U.S. in 1993, which served as an alert not only for American physicians but also for physicians in other countries for the identification of the disease. In the city of São Paulo, Brazil, 3 cases of the syndrome were recorded in 1993. The patients were young brothers residing in the Mata Atlântica (Atlantic Forest) region submitted to recent deforestation. Two of the patients died of acute respiratory insufficiency and the third recovered without sequelae. In the surviving patient the diagnosis was established by a laboratory criterion based on the detection of specific IgM and IgG class antibodies by indirect immunofluorescence. In the two patients who died, the diagnosis was confirmed by laboratory tests using immunoperoxidase technique for hantavirus in tissue, in histological lung and heart sections in one case, and by clinical and epidemiological data in the other Síndrome pulmonar por hantavírus. Relato dos três primeiros casos em São Paulo, Brasil O síndrome pulmonar por hantavírus foi reconhecido a partir dos casos ocorridos nos EUA em 1993. Esse alerta serviu tanto para os médicos americanos como para os de outros países na identificação de casos dessa doença. Na cidade de São Paulo, Brasil, em 1993, foram registrados 3 casos com essa manifestação da hantavirose; eram irmãos, do sexo masculino, jovens, residentes na região da Mata Atlântica, com desmatamento recente. Dois dos casos evoluíram para a morte causada por insuficiência respiratória aguda e o terceiro com recuperação sem seqüelas. No paciente sobrevivente o diagnóstico foi estabelecido por critério laboratorial pela pesquisa de anticorpos específicos das classes IgM e IgG pela técnica de imunofluorescência indireta. Dos casos que evoluíram para o óbito, um foi confirmado laboratorialmente pela técnica de imuno-histoquímica para hantavírus em tecido, em cortes histológicos de pulmão e coração; e no outro o diagnóstico foi clínico e epidemiológico